DEVELOPMENT TRENDS OF REMOTE WORK IN UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the development trends of remote work in Uzbekistan. The role of remote work in the process of high globalization , its importance in the country's economy and its current state are considered. At the same time, the factors influencing the development of remote work are considered. The study was based on statistical data, foreign experience and analysis of local conditions.